2016
DOI: 10.3109/00365521.2015.1107620
|View full text |Cite
|
Sign up to set email alerts
|

Placebo-controlled, randomised clinical trial: high-dose resveratrol treatment for non-alcoholic fatty liver disease

Abstract: In this placebo-controlled, high-dose and long-term study, resveratrol treatment had no consistent therapeutic effect in alleviating clinical or histological NAFLD, though there may be a small ameliorating effect on liver function tests and liver fat accumulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
149
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(161 citation statements)
references
References 36 publications
10
149
2
Order By: Relevance
“…In contrast to these encouraging studies, another very recent, randomized, clinical trial from Denmark including 28 patients with overweight found no indication that RES treatment (1.5 g RES/day for 6 months) had any consistent therapeutic effects (63). In line, a recent systematic review and meta-analysis study published during the revision of the current review concluded that the current evidence was insufficient to support the efficacy of resveratrol in the management of NAFLD (64).…”
Section: Res As a Therapeutically Effective Drug In Human Liver Diseasecontrasting
confidence: 43%
“…In contrast to these encouraging studies, another very recent, randomized, clinical trial from Denmark including 28 patients with overweight found no indication that RES treatment (1.5 g RES/day for 6 months) had any consistent therapeutic effects (63). In line, a recent systematic review and meta-analysis study published during the revision of the current review concluded that the current evidence was insufficient to support the efficacy of resveratrol in the management of NAFLD (64).…”
Section: Res As a Therapeutically Effective Drug In Human Liver Diseasecontrasting
confidence: 43%
“…Two included RCTs showed a beneficial effect of resveratrol in comparison with the lifestyle modification alone [11,19]. In contrast, the other two RCTs reported that resveratrol has no consistent therapeutic benefit in the management of NAFLD [10,18]. We could not perform a further subgroup analysis based on patients' characteristics due to the unavailability of relevant data.…”
Section: Summary Of the Main Resultsmentioning
confidence: 99%
“…Among the four included RCTs, two trials included only overweight or obese patients diagnosed with NAFLD [10,18]. In two trials resveratrol was administrated at a dose of 300mg and 500mg for three months [11,19], in one study at a dose of 1500mg daily for six months [18], and in one study a dose of 3000mg daily was utilized and followed up the patients were followed-up only for two months [10].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Downregulated Sphk1 could ameliorate inflammatory response, glomerular, and interstitial fibrosis in AN, eventually delaying the progress of FSGS. In fact, several clinical trials have already reported that RSV consumption improved neurovascular coupling capacity in adults with type 2 diabetes mellitus [33], decreased oxidized LDL and ApoB in patients undergoing primary prevention of cardiovascular disease [34,] and could ameliorate liver function tests and liver fat accumulation in non-alcoholic fatty liver disease [35]. However, no reports revealed the therapeutic effect of RSV in alleviating clinical or histological FSGS.…”
Section: Discussionmentioning
confidence: 99%